NGOs and the sociocultural adaptation of refugees: exploring challenges and impact - Demir, Cenker Korhan; Aldaoud, Jawan; Türkan, Aynur; Demir, Cenker Korhan (Routledge, 2025)
This study explores the role of non-governmental organisations (NGOs) in facilitating the sociocultural adaptation of Syrian refugees in Türkiye. Data were collected using both quantitative and qualitative methods, including a questionnaire featuring the Sociocultural Adaptation Scale – Revised, demographic and open-ended questions directed at refugees, and interviews with NGO representatives. The findings highlight both the successes and challenges associated with NGO-led programmes aimed at enhancing refugees’ sociocultural adaptation. While these initiatives have fostered environments that promote communication and mutual understanding between refugees and the host community, the study found that NGO programmes were positively associated primarily with language proficiency (LP), with beneficiaries demonstrating higher LP scores compared to non-participants. However, NGO programmes did not significantly influence overall sociocultural adaptation, and socio-demographic factors such as age and employment status were independently associated with LP outcomes. Respondents identified organisational deficiencies, a lack of expertise among training personnel, and the short duration of programmes as key obstacles. Language barriers were particularly challenging, exacerbated by economic pressures that hindered full-time educational engagement. Additionally, perceptions of non-acceptance from the host community, fuelled by political rhetoric and negative media portrayals, further complicated integration efforts. The study underscores the importance of multisectoral collaboration, to ensure more comprehensive integration.
Keywords: Syrian refugees sociocultural adaptation; NGO; Türkiye integration